Mineralocorticoid Receptor Antagonism in Patients With Atrial Fibrillation: Findings From the ORBIT‐AF (Outcomes Registry for Better Informed Treatment of Atrial Fibrillation) Registry. Issue 8 (11 September 0207) - Fudim, Marat; Liu, Peter R.; Shrader, Peter; Blanco, Rosalia G.; Allen, Larry A.; Fonarow, Gregg C.; Gersh, Bernard J.; Kowey, Peter R.; Mahaffey, Kenneth W.; Hylek, Elaine; Go, Alan S.; Thomas, Laine; et al.
Abstract : Background: Mineralocorticoid receptor antagonist (MRA) therapy may be beneficial to patients with atrial fibrillation (AF), but little is known about their use in patients with AF and subsequent outcomes. Methods and Results: In order to better understand MRA use and subsequent outcomes, we performed a retrospective cohort study of the contemporary ORBIT‐AF (Outcomes Registry for Better Informed Treatment of Atrial Fibrillation) registry. AF progression and cardiovascular outcomes were compared using propensity‐matched Cox proportional hazards modeling according to MRA use at baseline and new MRA use at follow‐up versus patients with no MRA use. Among 7012 patients with nonpermanent AF, 320 patients were taking MRA at enrollment, and 416 patients initiated MRA use during follow‐up. The mean patient age was 72.5 years, 56.3% were men, and 70.4% had paroxysmal AF. Among all patients taking MRAs, 434 (59.0%) had heart failure, 655 (89.0%) had hypertension, and 380 (51.6%) had both. After adjustment, new MRA use was not associated with reduced AF progression (hazard ratio, 1.18; 95% confidence interval, 0.88–1.58; P =0.27) but showed a trend towards lower risk of stroke, transient ischemic attack, or systemic embolism (hazard ratio, 0.17; 95% confidence interval, 0.02–1.23; P =0.08). Results were similar for a comparison of new MRA users and baseline MRA users compared with nonusers. Conclusions: In community‐based outpatients with AF, the majority of MRA use was for heart failure and hypertension. MRA use also trended towards lower adjusted stroke risk. Future studies should test the hypothesis that MRA use may decrease the risk of stroke in patients with AF.